PP25 Decision-making in ambulance service non-conveyance – the DMASC survey. Issue 1 (14th January 2019) - Black, Sarah; Frampton, Ian
Abstract : Background: A variety of factors influence the decision making of pre-hospital clinicians when considering conveying patients to the Emergency Department. This study aimed to explore the utility of a novel psychometric tool that identifies elements involved in the decision to leave a patient at scene following a 999 call. Methods: The Decision-making in Ambulance Service non-Conveyance (DMASC) Scale was used to survey 350 pre-hospital clinicians from one NHS Ambulance Trust. Items pertaining to four subscales: the autonomy with which non-conveyance decisions were made; steps taken to safeguard those decisions; the impact of previous experience; and patient characteristics influencing the decision, were explored. The DMASC scale was followed by the REI-40, a validated psychometric survey that determines preferred decision-making style. Results: Responses from 121 participants indicated clinicians felt they make autonomous decisions, with little involvement of other Health Care Professionals. There were no overall significant differences between clinical grades and DMASC scores, although there was a significant interaction between grade and the subscales Experience and Patient Characteristics, more skilled practitioners scored higher. There was no overall difference in the length of service and DMASC score, although there was a significant difference between staff in post <2 years, and those in post for between 7–15 years on the Safety Netting subscale. Scores from the REI-40 showed no overall significant differences between clinical grades, although those with between 3–6 years' experience scored significantly higher on the Rational scale than those with 7–15 years' experience. Conclusions: Implications for practice arising from these Results indicate clinical mentorship of newly qualified paramedics should be formalised to support safe decision-making when leaving patients at home. It also suggests that Specialist Paramedics may be using different decision-making heuristics than other grades to inform their confidence in leaving patients at the scene.